Flipped Classroom; Inovasi Pengaturan Lingkungan Belajar dalam Pembelajaran Matematika - Annajmi, Annajmi; Dedi Kuswandi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Innovation in learning can be done by changing the paradigm of mathematics teaching and inspiring teachers to provide alternative learning environment settings and gain new experiences. The flipped classroom (FC) is currently an innovative pedagogical approach that has the opportunity to transform mathematics learning in the future. The tasks given by teachers, teacher feedback and scaffolding, as well as the changing teaching and learning environment at FC provide a new paradigm for mathematics teachers in learning to meet student characteristics that are different from previous times. The aim of this research is to theoretically and conceptually reveal the Flipped Classroom as a learning environment setting in mathematics learning with a blended form of learning that reverses the traditional classroom learning environment by delivering teaching content, via video or other sources outside the classroom. This research uses a conceptual literature review with a descriptive approach. FC-based learning environment settings, students will watch learning material via videos on online platforms or other, students can collaborate in discussions or individually, or carry out experiments at home and be actively involved in applying concepts in the classroom guided by a teacher. Well-designed FC offers great opportunities to improve students' mathematical thinking and understanding. In this regard, FC is recommended for teachers to use as a setting for a mathematics learning environment in the future, which is appropriate to the characteristics of students in the digital era.